PRINCIPAL DIRECTIONS OF ECOLOGICAL ACCULTURATION IN FISHING INDUSTRY - Irina А. Dudakova; Igor G. Fomenko (Advanced Engineering Research)
Environmental problems are considered. The environmental impact on the production standards is defined. Principal directions of the ecological acculturation in the fishing industry are specified.